Genetic diversity amongst oat (Avena sativa) lines for micronutrients and agro-morphological traits - RANJAN, RAJEEV; CHAND, SUBHASH; INDU,; SINGHAL, RAJESH KUMAR; RANA, MANEET; SAH, R P; GAJGHATE, RAHUL; AHMED, SHAHID; DWIVEDI, KRISHNA KUMAR (The Indian Journal of Agricultural Sciences, 2024)
The present experiment was conducted during winter (rabi) seasons of 2019–20 and 2020–21 at the ICAR-Indian Grassland and Fodder Research Institute, Jhansi, Uttar Pradesh to study the genetic diversity amongst oat (Avena sativa L.) lines for micronutrients and agro-morphological traits. For study, 150 oat accessions collected from different sources were evaluated for two years and four micronutrients (Zn, Cu, Fe and Mn) and 9 agro-morphological traits were recorded. Genotypes IG02122 (464.0 mg/kg), IG02156 (48.1 mg/kg), IG03271 (136.0 mg/kg), and IG03213 (22.0 mg/kg) had maximum Fe, Zn, Mn and Cu content in fodder (harvested at 50% flowering). Genotype IG0280 had both high Zn (36.97 mg/kg) and Mn (114.33 mg/kg); IG03233 had high Cu (18.0 mg/kg) and Mn (124.0 mg/kg); and IG02131 had high Cu (18.33 mg/kg) and Fe (369.0 mg/kg) content. Analysis of variance (ANOVA) highlighted significant genotypic differences (P